2011
DOI: 10.1016/j.theriogenology.2010.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Systemic treatment with high dose of flunixin-meglumine is able to block ovulation in mares by inducing hemorrhage and luteinisation of follicles

Abstract: Prostaglandins play an obligatory role during the process of ovulation in mammals. Ovulation can be blocked by intrafollicular administration of non-steroidal anti-inflammatory drugs (NSAIDs) in several domestic species including the mare as well as by systemic administration of these drugs in women. In the mare, the effect of systemic NSAIDs treatment on ovulation has not been critically studied. The objectives of this study were: a) to determine whether high dose of flunixin-meglumine (FM) administered syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
6
21
1
Order By: Relevance
“…The percentage of LUFs in our study was higher than the 83% incidence of LUFs reported following FM treatment in mares (Cuervo-Arango & Domingo-Ortiz 2011) and the 36% incidence following treatment with higher doses of COX-2 inhibitor (meloxicam) in women (Jesam et al 2014). The increased incidence of LUFs in the present study was, in part, attributed to a higher dose of FM in our study compared to previous study , and/or to a lower dose (1500 IU) of hCG in our study vs 2500 IU in a previous study , Cuervo-Arango & Domingo-Ortiz 2011. Therefore, it seems that for proper experimental induction of LUFs, an optimum balance between ovulatory stimulus (hCG) and an adequate decrease of intrafollicular prostaglandin (by the use of COX-2 inhibitor) must be achieved.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The percentage of LUFs in our study was higher than the 83% incidence of LUFs reported following FM treatment in mares (Cuervo-Arango & Domingo-Ortiz 2011) and the 36% incidence following treatment with higher doses of COX-2 inhibitor (meloxicam) in women (Jesam et al 2014). The increased incidence of LUFs in the present study was, in part, attributed to a higher dose of FM in our study compared to previous study , and/or to a lower dose (1500 IU) of hCG in our study vs 2500 IU in a previous study , Cuervo-Arango & Domingo-Ortiz 2011. Therefore, it seems that for proper experimental induction of LUFs, an optimum balance between ovulatory stimulus (hCG) and an adequate decrease of intrafollicular prostaglandin (by the use of COX-2 inhibitor) must be achieved.…”
Section: Discussioncontrasting
confidence: 46%
“…Similarly, intrafollicular or systemic administration of prostaglandin inhibitors has been shown to cause luteinization of follicles in rats (Armstrong & Grinwich 1972), rabbits (Salhab et al 2003), mares (Watson & Sertich 1991, Cuervo-Arango & Domingo-Ortiz 2011, and women (Killick & Elstein 1987, Priddy et al 1990, Jesam et al 2010, 2014. In mares, flunixin meglumine (FM) at a dose rate of 1.7 or 2.0 mg/kg body weight has been shown to induce LUFs in 73-83% of mares respectively , Cuervo-Arango & Domingo-Ortiz 2011. Furthermore, intrafollicular administration of prostaglandins has successfully prevented FM-induced LUF formation, allowing subsequent ovulation and conception in mares (Martínez-Boví & Cuervo-Arango 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Its obligatory role in ovulation has been proven by several studies in which their synthesizing enzyme (PGHS-2) was inhibited by systemic treatment with flunixinmeglumine (FM), a non-steroidal anti-inflammatory drug (Cuervo-Arango and Domingo-Ortiz 2011;Cuervo-Arango 2011). The majority of mares treated intravenously with FM during the periovulatory period did not ovulate but developed a luteinized unruptured follicle (LUF; Cuervo-Arango et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…From all molecular factors involved in ovulation, the enzyme prostaglandin G/H synthase-2 (PGHS-2) present in granulosa cells and its products prostaglandins F 2a and E 2 in follicular fluid have been extensively studied in laboratory animals [2], women [3], cows [4], ewes [5], and mares [6,7]. In all these species, the blockade of PGHS-2 by nonsteroidal anti-inflammatory drugs during the periovulatory period inhibited ovulation in a large percentage of treated females and induced the formation of luteinized unruptured follicles (LUFs).…”
Section: Introductionmentioning
confidence: 99%